2016
DOI: 10.1136/bmj.i3633
|View full text |Cite
|
Sign up to set email alerts
|

Adverse obstetric outcomes after local treatment for cervical preinvasive and early invasive disease according to cone depth: systematic review and meta-analysis

Abstract: Objective To assess the effect of treatment for cervical intraepithelial neoplasia (CIN) on obstetric outcomes and to correlate this with cone depth and comparison group used.Design Systematic review and meta-analysis.Data sources CENTRAL, Medline, Embase from 1948 to April 2016 were searched for studies assessing obstetric outcomes in women with or without previous local cervical treatment.Data extraction and synthesis Independent reviewers extracted the data and performed quality assessment using the Newcast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
328
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(347 citation statements)
references
References 119 publications
8
328
0
11
Order By: Relevance
“…Uterine and cervical weakness impair their ability to support mechanical stresses induced by full-term pregnancy. Mechanical weakness is thought to contribute to PTB in women with uterine anomalies, previous cervical surgery, more than 3 prior abortions, or an interpregnancy interval of less than 6 months (3,(22)(23)(24). Multiple pregnancies can also cause over-distention of the uterus and release of pro-inflammatory cytokines, leading to contractions and P-PROM (7).…”
Section: Aetiology and Risk Factors For Ptbmentioning
confidence: 99%
“…Uterine and cervical weakness impair their ability to support mechanical stresses induced by full-term pregnancy. Mechanical weakness is thought to contribute to PTB in women with uterine anomalies, previous cervical surgery, more than 3 prior abortions, or an interpregnancy interval of less than 6 months (3,(22)(23)(24). Multiple pregnancies can also cause over-distention of the uterus and release of pro-inflammatory cytokines, leading to contractions and P-PROM (7).…”
Section: Aetiology and Risk Factors For Ptbmentioning
confidence: 99%
“…The general aim of this thesis is to inform decision-makers about the health benefits, resource use and cost-effectiveness of current and future CC screening policies in Norway. Specifically, the four papers in this thesis evaluate: (i) the short-term health and economic outcomes of using novel biomarkers to triage younger (i.e., aged [25][26][27][28][29][30][31][32][33] years) unvaccinated women with minor cervical cytological lesions, (ii) the most costeffective strategy to triage unvaccinated women with minor cervical cytological lesions, (iii) the trade-offs in health benefits and resource use associated with adopting primary HPV DNA testing strategies for unvaccinated women, and (iv) the most cost-effective CC screening strategies for women vaccinated against HPV-infections in adolescence.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Women may also experience anxiety from the procedure itself, or from awaiting and receiving test results. In addition, diagnostic colposcopy-directed biopsy may cause pain, bleeding, or discharge [29], and treatment of cervical precancer is associated with an increased risk of preterm birth and other adverse pregnancy outcomes [30,31]. The majority of precancers would never have progressed to cancer in the absence of treatment [22] yet available technologies cannot distinguish between precancers that will progress to CC from those likely to regress; consequently, CC screening involves some over-treatment.…”
Section: Principles and Aspects Of Cervical Cancer Screeningmentioning
confidence: 99%
“…screening tests and between 300 and 900 excisional procedures (e.g., loop electrosurgical excision procedure or cone biopsy). 10 Furthermore, a systematic review and meta-analysis that assessed the effect of treatment for cervical intraepithelial neoplasia on obstetric outcomes 11 showed that cervical excisional procedures may increase the rate of preterm birth by about 5%, depending on the depth of excision, and raise the risk of perinatal death by about 0.2% in each subsequent pregnancy, yet the cumulative risk of cancer developing before age 30 years is less than 0.05%. In addition, diagnosis of cervical intraepitheleal neoplasia has substantial psychosocial impact, particularly for women with high-grade lesions.…”
Section: Key Pointsmentioning
confidence: 99%